Testes de estresse na avaliação do vigor de sementes de milho - Souza Grzybowski, Camila Ribeiro de; Vieira, Roberval Daiton [UNESP]; Panobianco, Maristela (Univ Federal Ceara, Dept Geol, 2015)
When sowing maize, such adverse factors as flooding and temperatures below those recommended can hinder establishment of the stand. There is therefore a need to find alternatives for the determination of seed vigour under adverse conditions, with a view to helping the system of production. This work aimed to estimate the physiological quality of maize seed under conditions of hydric and thermal stress, studying the methodology of testing by submersion in water and germination at low temperatures. To carry out the experiments, ten lots of two single hybrids (30F35R and 30P70H) were used, giving five lots of each. Evaluation of the initial quality of the lots was determined by water content, the cold test and the tests of germination and seedling emergence; the methodologies studied to evaluate vigour were: a) submersing the seeds in water, combining different periods (24, 36, 48 and 72 hours) and temperatures (20, 25 and 30 degrees C); and b) germination at low temperature, testing at 15 degrees C for eight days and at 16, 17 and 18 degrees C for seven days. The test for submersion in water is promising for the evaluation of the vigour of maize seeds under conditions of stress through immersion of the seeds in water for 48 hours at 25 degrees C.

Na semeadura da cultura do milho, fatores adversos como o alagamento do solo e temperaturas abaixo da recomendada podem prejudicar o estabelecimento do estande. Assim, há a necessidade de se buscar alternativas para a determinação do vigor da semente em condições adversas, visando auxiliar o sistema de produção. No trabalho objetivouse estimar a qualidade fisiológica de sementes de milho em condições de estresses hídrico e térmico, estudando a metodologia dos testes de submersão em água e germinação a baixa temperatura. Para condução dos experimentos foram utilizados dez lotes de dois híbridos simples (30F35R e 30P70H), sendo cinco de cada. A avaliação da qualidade inicial dos lotes foi determinada pelo teor de água e testes de germinação, frio e emergência de plântulas e, as metodologias estudadas para a avaliação do vigor foram: a) submersão das sementes em água, combinando diferentes períodos (24; 36; 48 e 72 horas) e temperaturas (20; 25 e 30 °C); b) germinação a baixa temperatura, testando-se 15 °C por oito dias e 16; 17 e 18 °C por sete dias. O teste de submersão em água é promissor para avaliação do vigor de sementes de milho em condições de estresse, mediante imersão das sementes em água por 48 horas, a 25 °C.
Stress testing in the evaluation of vigour in maize seed
Keywords: Zea mays L.; Germination; Submersion in water; Low temperature; Zea mays L.; Germinação; Submersão em água; Baixa temperatura